Subject-specific instructional methods and activities - Brophy, Jere E. (Advances in research on teaching ;, 2001)
This volume explores the tension between the search for generic principles of good teaching that cut across school subjects and the belief that portrayals of best practices ought to be framed separately for each subject. Its contributors all favor teaching in ways that encourage students to learn each subject with understanding of its big ideas, appreciation of its value, and acquisition of the disposition to apply it in their lives outside of school. They consider curricular, instructional, and assessment aspects of best practices that foster this kind of learning in fourteen school subjects, focusing on instructional methods and learning activities. In the introduction, Editor Jere Brophy presents twelve generic guidelines for good teaching that he believes represent current consensus about best practices that should be applicable to any school subject. Then, leading scholars concerned with curriculum and instruction in particular school subjects (beginning reading, content area reading and literature studies, writing, number, geometry, biology, physics, chemistry, earth science, history, physical geography, cultural studies, citizenship education, and economics) synthesize current thinking about best practices in teaching their respective subjects, commenting on the applicability of generic principles but focusing on subject-special goals and methods. These state-of-the-field contributions take into account not only relatively formal research, but also the wisdom of practice as represented in standards documents, case studies of good teaching, and the methods and activities commonly recommended in subject-specific teacher education texts. The fourteen chapters examine best practices with a much closer lens than more conventional approaches that consider language arts, mathematics, science, and social studies teaching in general but do not focus on the strands that compose these four broad curricular areas. In a final discussion chapter, Brophy draws from these chapters to reassess the applicability of generic guidelines across subjects and to identify commonalities and points of contention in what the authors have to say about instructional materials, content representations, discourse management, learning activities, assessment, technology, and other factors involved in teaching school subjects effectively.